Development, characterization and cell viability inhibition of pva spheres loaded with doxorubicin and 4′-amino-1-naphthyl-chalcone (D14) for osteosarcoma - Seba, Viviane; de Lima, Gabriel Goetten; Pereira, Bruno L.; Silva, Gabriel; Reinhardt, Luiza Steffens; Arantes, Pablo Ricardo; Chee, Bor Shin; Dos Santos, Mariana Bastos [UNESP]; França, Suzelei C.; Regasini, Luis Octavio [UNESP]; Fachin, Ana Lúcia; Cao, Zhi; et al. (MDPI, 2021)
Chalcones (1,3-diaryl-2-propen-1-ones) are naturally occurring polyphenols with known anticancer activity against a variety of tumor cell lines, including osteosarcoma (OS). In this paper, we present the preparation and characterization of spheres (~2 mm) from polyvinyl alcohol (PVA) containing a combination of 4′-Amino-1-Naphthyl-Chalcone (D14) and doxorubicin, to act as a new polymeric dual-drug anticancer delivery. D14 is a potent inhibitor of osteosarcoma progression and, when combined with doxorubicin, presents a synergetic effect; hence, physically crosslinked PVA spheres loaded with D14 and doxorubicin were prepared using liquid nitrogen and six freeze–thawing cycles. Physical-chemical characterization using a scanning electron microscope (SEM), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) presented that the drugs were incorporated into the spheres via weak interactions between the drugs and the polymeric chains, resulting in overall good drug stability. The cytotoxicity activity of the PVA spheres co-encapsulating both drugs was tested against the U2OS human osteosarcoma cell line by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, and compared to the spheres carrying either D14 or doxorubicin alone. The co-delivery showed a cytotoxic effect 2.6-fold greater than doxorubicin alone, revealing a significant synergistic effect with a coefficient of drug interaction (CDI) of 0.49. The obtained results suggest this developed PVA sphere as a potential dual-drug delivery system that could be used for the prominent synergistic anticancer activity of co-delivering D14 and doxorubicin, providing a new potential strategy for improved osteosarcoma treatment.
Keywords: Chalcone; Doxorubicin; Freeze–thaw; Osteosarcoma; PVA